Combining observations and numerical model results to improve estimates of hypoxic volume within the Chesapeake Bay, USA. Issue 10 (3rd October 2013) - Bever, Aaron J.; Friedrichs, Marjorie A. M.; Friedrichs, Carl T.; Scully, Malcolm E.; Lanerolle, Lyon W. J.
<x xml:space="preserve">Abstract</x> [1] The overall size of the "dead zone" within the main stem of the Chesapeake Bay and its tidal tributaries is quantified by the hypoxic volume (HV), the volume of water with dissolved oxygen (DO) less than 2 mg/L. To improve estimates of HV, DO was subsampled from the output of 3‐D model hindcasts at times/locations matching the set of 2004–2005 stations monitored by the Chesapeake Bay Program. The resulting station profiles were interpolated to produce bay‐wide estimates of HV in a manner consistent with nonsynoptic, cruise‐based estimates. Interpolations of the same stations sampled synoptically, as well as multiple other combinations of station profiles, were examined in order to quantify uncertainties associated with interpolating HV from observed profiles. The potential uncertainty in summer HV estimates resulting from profiles being collected over 2 weeks rather than synoptically averaged ∼5 km3. This is larger than that due to sampling at discrete stations and interpolating/extrapolating to the entire Chesapeake Bay (2.4 km3). As a result, sampling fewer, selected stations over a shorter time period is likely to reduce uncertainties associated with interpolating HV from observed profiles. A function was derived that when applied to a subset of 13 stations, significantly improved estimates of HV. Finally, multiple metrics for quantifying bay‐wide hypoxia were examined, and cumulative hypoxic volume was determined to be particularly useful, as a result of its insensitivity to temporal errors and climate change. A final product of this analysis is a nearly three‐decade time series of improved estimates of HV for Chesapeake Bay.